A STUDY OF BEHAVIOURAL FINANCE AND ITS IMPACT ON INVESTMENT DECISION OF WOMEN MICRO ENTREPRENEUR- A PILOT STUDY - Rajput, Vijaya B.; Samdariya, Payal (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The main objective is to study the various behavioural biases which are going to impact on the women micro entrepreneur investment decision. On respect of that mainly we are study the six main behavioural biases which include the Overconfidence Bias, Heuristic Bias, Availability Bias, Optimisms Bias, Loss Aversion Bias, Disposition Effect. For studying this research topic we are also analyse some other factors such as Anchoring Bias, Regret Aversion Bias, Confirmation Bias, Herd Behaviour etc. which are also going to impacted on the investment decision. The cross sectional research is going to conduct to perform this research study and also helps arrive at the appropriate conclusion. This research study are mainly going to conducted in the Pune city having the population of 45,69,000 peoples. The primary data is collected from the 181 women micro-entrepreneur who run their business Pune city by using a simple random sampling method and secondary data collected from the existing research paper, journals, newspaper, research article to get the updated knowledge about the research topic. Questionnaire method are going to use for the purpose of collection of data with the help of the quantitative data are obtained. The descriptive statistics are going to for arriving at the appropriate conclusion.